(3JMQjQ GdbhGYO GdefWbjI aj TQM GdTeSjIs - (3GdQGRj, GdbWH GdJMJGfj, eMeO Hf eMeO, J (B766 (3g`s
(3ChdgG (B:s
(3HYO GdHSedI ; Ef CHgi OQQ JfXe HHfjGf GdHjGf HYO abO WGd EdMGM GdeTJZdjf Ydj Edi Cf CTQM dge GdQSGdI GdTeSjI hCHjf ajg bhGYO GdefWbjI hTQMJgG TQMG cTa GdCUOGa Yf hLhg aQGjO ahGjOgG hSejJg HJMQjQ GdbhGYO GdefWbjI aj TQM QSGdI GdTeSjIs
(3BNQgG (B:s
(3NGQLI Yf ehVhYGJgG ddGeJfGY Cf jchf LRA GdTjA eWdhHG KHhJg dg HGdQHgGJ dCf GdCLRGAs
(3aj Chdg fbhd HGdYQHjI hGdJQcjI hehGYXs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B7/38s
(3eYLe GdeDdajf (B3/642s
(3cTa GdXfhf (B2/ 1063s
(3TPQGJ GdPgH (B6/207s
Keywords: (3GdadSaI hGdefWbs